Penyelesaian Ganti Rugi Tanah Milik dan Tanam Tumbuh Pengadaan Tanah Lahan Pengembangan Cagar Budaya Nasional Kabupaten Muaro Jambi - Hariss, Abdul; Fauzia, Nur (Wajah Hukum, 2025)
Procurement of land for public purposes is the implementation of the social function of land rights. Therefore, every person who has rights to land is required to relinquish his rights to land for the sake of the public interest, including the interests of the nation and state as well as the common interests of the people. For the procurement of land for public purposes, each person is entitled to compensation from the state as occurred in the procurement of land for development of the National Cultural Heritage of Muaro Jambi Regency. Every person whose land, whether in the form of property rights or planting rights, grows into and/or is affected by the object of procurement must be given compensation. However, in reality, the process of land acquisition for public purposes is not free from many obstacles because it is related to the interests of many people. The study in this scientific work relates to forms of compensation for the community, obstacles in the compensation process and the efforts made by the government to overcome the obstacles present in the compensation process for freehold land and growing planting land for land acquisition for cultural heritage development in Muaro Jambi. The research approach was carried out socio-legally with primary data and secondary data.